The effect of ankle flexibility on the relationship between knee isokinetic strength and the speed of underwater dolphin kicks in male competitive swimmers - Shen, Y.; Fu, Y.; Ge, Y.; Wen, Y. (Isokinetics and Exercise Science, 2022)
BACKGROUND: Lower-extremity muscle strength and ankle flexibility play key roles in underwater swimming movements. OBJECTIVES: To investigate the relationship between knee isokinetic strength and the speed of underwater dolphin kicks (UDK-S) in competitive male swimmers and identify whether ankle flexibility affects the association between knee isokinetic strength and UDK-S. METHODS: Fifty-two highly trained male swimmers participated in this study. The speed at which the participants travelled 15 m performing UDKs was calculated as UDK-S. Knee flexor and extensor concentric isokinetic strength at fast (240°/s) and slow (60°/s) velocities and ankle flexibility were evaluated. Bayesian framework analysis was conducted to examine the relationship between these variables and determine whether this relationship is influenced by ankle flexibility. RESULTS: There was strong-to-extremely strong evidence (Bayes factor = 24.4 to 198.3) that knee extensor (60°/s) and knee flexor (60°/s and 240°/s) strength are positively and generally moderately correlated with UDK-S. Ankle plantar flexion flexibility was identified to be a moderator between knee extensor strength (60°/s) and UDK-S. CONCLUSIONS: Knee extensor and knee flexor strength were significantly correlated with UDK-S, and the relationship between knee muscle strength and UDK-S was influenced by ankle plantar flexion flexibility in male competitive swimmers.